Galvanic Corrosion and Ion Release from Different Orthodontic Brackets and Wires in Acidic Artificial Saliva - Tahmasbi, Soodeh; Ghorbani, Mohammad; Sheikh, Tahere; Yaghoubnejad, Yadollah (Journal of Dental School, 2019)
Objective: Corrosion resistance is among the most important properties of metal alloys used in the oral cavity. Consumption of acidic foods reduces the salivary pH and intensifies the corrosion of brackets and orthodontic wires. This study aimed to compare electro galvanic corrosion of different orthodontic brackets and wires and determine the amount of ions released into acidic artificial saliva. Methods: In this in vitro experimental study, 24 mandibular incisor brackets of 4 different manufacturers (Dentaurum, American Orthodontics, Shinye and ORJ) with stainless steel (SS) or nickel-titanium (Ni-Ti) round wires 0.016 were immersed in acidic artificial saliva for 28 days and their potential difference with the reference electrode was recorded. The amount of released ions was measured in the solution using atomic absorption method. Data were analyzed using two-way ANOVA and repeated measures ANOVA. Results: The mean amount of ions released was not significantly different between groups (p>0.05). The potential difference of Shinye brackets coupled to SS wire was significantly lower than that of other combinations and was negative throughout the study. The potential difference of Dentaurum bracket-NiTi wire, ORJ bracket-NiTi wire, Shinye bracket-SS wire and ORJ bracket-SS wire combinations at the end of experiment was negative as well. Conclusion: The galvanic corrosion of Shinye bracket coupled to SS wire in acidic artificial saliva was greater than that of other bracket-wire combinations. The specimens were not significantly different in terms of the released ions.